2002
DOI: 10.1002/1521-3773(20020916)41:18<3429::aid-anie3429>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A C2v-Symmetric Barbaralane

Abstract: A homoaromatic C2v‐symmetric tetraphosphabarbaralane is the candidate for the first barbaralane derivative with “inverse” barrier to Cope rearrangement according to quantum chemical calculations (see scheme) as its Cs‐symmetric form with localized double bonds is higher in energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Analogously to 1 , the introduction of heteroatoms in the related fluxional molecule barbaralane has been investigated. Experimentally, 2,4,6,8‐tetraazasubstitution slightly reduces the barrier of the Cope rearrangement,33 and two heterobarbaralenes were shown to have homoaromatic ground states using ab initio computational methods 34, 35…”
Section: Introductionmentioning
confidence: 99%
“…Analogously to 1 , the introduction of heteroatoms in the related fluxional molecule barbaralane has been investigated. Experimentally, 2,4,6,8‐tetraazasubstitution slightly reduces the barrier of the Cope rearrangement,33 and two heterobarbaralenes were shown to have homoaromatic ground states using ab initio computational methods 34, 35…”
Section: Introductionmentioning
confidence: 99%
“…Hoffmann and Dewar , suggested substituents for stabilizing the transition structure for the Cope rearrangement of semibullvalene relative to the two degenerate localized structures and proposed that substituents might even reverse the relative energies of the localized and delocalized structures. Substitution of heteroatoms such as nitrogen, , phosphorus, and boron carbonyl for CH groups in semibullvalenes and barbaralanes has also been predicted to favor delocalized structures over localized structures. In addition, annelation strategies, which employ strain to destabilize the localized semibullvalene structures and thus to favor the delocalized geometries, have been proposed. , The relative importance of ground-state strain and bishomoaromatic stabilization in Cope transition structures of fluxional molecules has recently been analyzed .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical analyses by Hoffmann and Dewar suggested that electron-withdrawing groups at C 2,8 and C 4,6 , as well as electron-donating groups at C 1,5 , might stabilize the bishomoaromatic transition state 2 preferentially and eliminate the barrier. In addition to these electronic effects, strain-induced destabilization of the localized structure 1 through small-ring annelations at C 2,8 or/and C 4,6 , ,, as well as stabilization of the delocalized structures through Li + coordination and heteroatom substitutions, have been explored. Despite extensive attempts, experimental realization of a definitive neutral bishomoaromatic semibullvalene is still elusive .…”
mentioning
confidence: 99%